Budaya dan Pendidikan Bahasa Penduduk Baru dalam Kebijakan Arah Selatan Baru Taiwan - Yufita Ng (Journal of Policy & Bureaucracy Management, 2020)
As an immigration country, Taiwan has a variety of cultures, both local and foreign cultures that are brought with by new immigrants, one of which is a new resident from Southeast Asia who settled in Taiwan because of transnational marriage between Southeast Asian women and Taiwanese men. The differences in culture, economic capacity, and educational level of Southeast Asian new residents with local Taiwanese create stigma and stereotypes in society, which then worsen due to a lack of communication and cultural introduction. To bridge the problem, Tsai Ing-wen government through the New Southbound Policy (NSP) is persistent in promoting the culture of new residents by organizing various routine cultural activities so that local Taiwanese understand and accept the new resident culture. Apart from promoting culture, the government has also established Southeast Asian languages as one of the mother tongues that can be learned in elementary school. To prepare for the procurement of Southeast Asian Languages lessons in the 2019 curriculum, starting in 2016 the government is developing textbooks for the primary and secondary school levels, as well as training 7 Southeast Asian language teachers, starting in 2017 some universities also hold proficiency tests for Southeast Asian language. Even though there are still obstacles, the development of culture and language shows positive results. The Established Southeast Asian Language Department and Southeast Asian Research Department by 4 Taiwanese universities have attested to the increasing interest in learning Southeast Asian languages and things.